High strain in (Bi1/2Na1/2)0.935Ba0.065TiO3–Sr3FeNb2O9 lead-free ceramics with giant piezoresponse. Issue 110 (22nd October 2015) - Cheng, Renfei; Wang, Chunmei; Xu, Zhijun; Chu, Ruiqing; Hao, Jigong; Li, Huaiyong; Li, Wei; Du, Juan; Li, Guorong
Abstract : This large EFIS at low applied field indicates that the BNBT–0.009SFN system is a potential candidate material for environmentally friendly electromechanical devices and actuator applications. Abstract : The structure, electric field-induced strain (EFIS), polarization and piezoelectric response of lead-free Sr3 FeNb2 O9 -modified (Bi1/2 Na1/2 )0.935 Ba0.065 TiO3 (BNBT– x SFN, with x = 0–0.012) ceramics were investigated. XRD patterns show that all compositions have a pure perovskite structure and SFN effectively diffused into the BNBT lattice during sintering to form a solid solution. A large EFIS of 0.35% was obtained at the critical composition of x = 0.009 which corresponds to a normalized strain ( S max / E max ) of 583 pm V −1 . A maximum value of piezoelectric constant (254 pC N −1 ) was obtained for x = 0.006. These results show our research can benefit the developments of Bi1/2 Na1/2 TiO3 ceramics and widen their range of applications.